Competencias docentes y enfoques de aprendizaje (Papeles, 2011)
This article, product of the processes derived from the research Assessment teaching and learning in the classroom, by the National Pedagogical University, shows that several concepts of competencies are highlighted as ineluctable for a competent teacher action: didactic knowledge of their specific discipline and its contextual nature and, finally, the generation of learning vocation. In line with this, the approaches superficial and deep are sketched setting the difference between declarative and functional knowledge. In the above context, we propose four teachers’ competencies to examine and discuss: didactics, transferable skills, research and social nature.
Keywords: competition; pedagogical knowledge specific to the discipline; learning approaches; declarative knowledge and fuctional knowledge